Edukasi Kompres Daun Sirih untuk Mempercepat Penyembuhan Luka Perineum pada Ibu Nifas di PMB Lina Contesa - Devina Anggrainy Dencik (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Perineal wounds are commonly experienced by postpartum mothers after vaginal delivery and may cause pain and increase the risk of infection if not properly managed. Appropriate perineal wound care, including the use of non-pharmacological methods, requires adequate maternal knowledge and skills. This program aimed to improve postpartum mothers’ knowledge and skills in perineal wound care through education on betel leaf compresses at PMB Lina Contesa. A community empowerment approach was applied through health education combined with demonstrations and hands-on practice. Evaluation was conducted by assessing changes in maternal knowledge and skills and by observational monitoring of perineal wound conditions. The results showed improvements in maternal knowledge and skills in performing perineal wound care using betel leaf compresses. In addition, postpartum mothers reported reduced pain and no signs of infection during the observation period. These findings indicate that education on betel leaf compresses has the potential to serve as an applicable promotive and preventive approach to support accelerated perineal wound healing among postpartum mothers in primary midwifery care setting.